Association of tuberculosis in patients with chronic myeloid leukemia: a treatment proposal based on literature review. Issue 2 (1st February 2021) - Iqbal, Phool; Soliman, Ashraf; De Sanctis, Vincenzo; Yassin, Mohamed A.
ABSTRACT: Introduction : Chronic Myeloid leukemia (CML) is one of the first hematological malignancy linked with genetic alterations and have a targeted therapy with Tyrosine Kinase Inhibitors. However, there are certain unanswered questions and many unmet needs which limit its treatment. Concurrent Mycobacterium Tuberculosis (Mtb) infection is one of those significant factors. Tuberculosis (TB) is a highly prevalent disease in association with diabetes mellitus, malignancy, poor socioeconomic environment, HIV, and other immunosuppressive conditions in developed and developing countries. Anti-TB medications can affect other drug's pharmacokinetics by altering liver enzymes metabolism and poses treatment challenge with CML medications. Areas covered : The authors performed a rigorous literature review between 2000 and 2020 using PubMed and Google Scholar, with the main focus on all articles addressing the topic of TB in CML. Authors highlighted the need to improve clinical diagnosis and to define management strategy for this dilemma. Expert opinion : In the current era, there are no clear guidelines or recommendations in the literature that address this problem. The aim of this review was to collect and carefully analyze the literature to highlight the need for comprehensive guidelines and propose an algorithm for better management of TB in patients with CML.